Implementasi QR Code Menggunakan Google Api dalam Membangun Sistem Informasi E-Bansos Menggunakan Metode Extreme Programming (Studi Kasus: Kelurahan Batujaya) - Irawan, Irawan; Nugroho, Fajar Agung (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Social assistance is a form of concern for the government or social organizations that are legal entities in overcoming poverty, natural disasters, or as currently all countries are being affected by the Covid 19 virus which has resulted in the economy in Indonesia itself weakening which makes people lack food. From these problems, social assistance is very much needed for people affected by the Covid 19 Virus, the social assistance needed is such as money, clothing, food, and medicine. From these problems can be solved with a web-based social assistance application built with the Extreme Programming Method. This Extreme Programming method with stages of planning, design, coding, and testing can make it easier for researchers to solve these problems. then a social assistance web application was built that can be accessed by the public to register and login to view the QR Code when receiving social assistance, while the admin is to manage social assistance and transactions.